PENGARUH RETURN ON ASSET (ROA) DAN DEBT TO ASSET RATIO (DAR) TERHADAP EARNING PER SHARE (EPS) PADA PT. MUSTIKA RATU Tbk PERIODE 2015-2024 - Savana, Savana Nabilla; Eni Puji Astuti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract.  This study aims to examine the effect of Return on Assets (ROA) and Debt to Asset Ratio (DAR) on Earnings per Share (EPS) at PT Mustika Ratu Tbk for the period 2015–2024, both partially and simultaneously. The data analysis methods used include Descriptive Statistical Analysis, Classical Assumption Tests, Multiple Linear Regression Analysis, Coefficient of Determination Test, Correlation Test, and Hypothesis Testing. The research conducted by the author in preparing this undergraduate thesis uses a descriptive method with a quantitative approach. The sample consists of the annual financial statements of PT Mustika Ratu Tbk for the period 2015–2024, while the population in this study includes all financial statements of PT Mustika Ratu Tbk. The results of the hypothesis testing using the t-test indicate that partially, the Return on Assets variable has a positive and significant effect on Earnings per Share at PT Mustika Ratu Tbk for the period 2015–2024, with a significance level of 0.001 < 0.05. Partially, the Debt to Asset Ratio does not have a significant effect on Earnings per Share at PT Mustika Ratu Tbk for the period 2015–2024, with a significance level of 0.043 < 0.05. Meanwhile, the results of the hypothesis testing using the F-test show that simultaneously, the variables Return on Assets and Debt to Asset Ratio do not have a positive and significant effect on Earnings per Share at PT Mustika Ratu Tbk for the period 2015–2024, with a significance level of 0.001 < 0.05.